Sex Differences in Patients With Different Stages of Knee Osteoarthritis - Logerstedt, David S.; Zeni, Joseph; Snyder-Mackler, Lynn (Archives of physical medicine and rehabilitation, 2014)
To quantify the differences in physical impairments and in performance-based measures and patient-reported outcomes in men and women seeking nonoperative management of symptomatic moderate knee osteoarthritis (OA) and those with symptomatic end-stage knee OA scheduled for total knee arthroplasty compared with healthy controls. Cross-sectional analysis of individuals referred to physical therapy, community participants, and subjects from a 2-year longitudinal study. University research department. Cross-sectional analysis of participants (N=289) consisting of a moderate OA group (n=83), a severe OA group (n=143), and a healthy control group (n=63). Not applicable. Quadriceps strength, timed Up and Go test, stair-climbing test, 6-minute walk test, Knee Outcome Survey–Activities of Daily Living Scale (KOS-ADLS), and Physical Component Summary (PCS) of the Medical Outcomes Study 36-Item Short-Form Health Survey. Women had worse scores than men for physical impairment and performance-based measures (P<.001). In the moderate OA group, women had significantly lower KOS-ADLS (P=.007) and PCS (P=.026) scores than men, with no differences seen between sexes in the other 2 groups for patient-reported measures. Differences between women and men with knee OA on physical impairments and performance-based measures are not echoed in the differences seen in patient-reported measures. These measures signal different domains of knee function in patients with knee OA and should be used as part of a comprehensive functional evaluation.